Quality management in a private speech-language therapy practice - Klop, Daleen (Division of Communication Sciences and Disorders, 2017)
This study investigated the principles of quality management and their application to a private speech-language therapy practice. The history of quality management and the development of quality management in industry and health care services were reviewed. Quality was defined in terms of the context of the author's private speech-language therapy practice and a working definition of quality was developed. The principles in the development of a quality management programme were described. These principles were used to develop and implement a quality management programme in the author's private speech-language therapy practice. Financial management and client satisfaction were selected as strategic quality factors in the initial stages of the quality management programme. Practice policies were revised to establish success criteria and to measure the practice's conformance to these criteria. The quality management programme enabled the author to improve the quality and effectiveness of her practice's financial management system and to demonstrate the client-centered orientation of the practice by implementing client satisfaction as a quality indicator.